2019
DOI: 10.1155/2019/2898691
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of Anastomotic Stenosis after Rectal Cancer Surgery Using a Circular Stapler and Colostomy with Double Orifice

Abstract: The double stapling technique has greatly facilitated intestinal reconstruction, particularly for anastomosis after anterior resection. However, anastomotic stenosis may occur, which sometimes requires surgical treatment. Redo surgery with reresection and reanastomosis presents a high risk of complications. Treatment methods need to be selected depending on the degree and location of stenosis. In an effort to propose a new resolution, reporting new cases and sharing valid experiences are necessary. An 82-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In addition, it is also very difficult to manage these anastomosis strictures. Although some authors suggest the resection of this area with circular stapler for the treatment of anastomosis strictures [55], this may not always be possible, since stricture often includes a long colon segment, as in our 3 patients in high ligation group, and sometimes surgery might have to be terminated with an end colostomy, especially in anastomoses located below. Also it can be thought that diversion colitis might be contributed to the high anastomosis stricture rate (28.2%) in the high ligation group in our study.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, it is also very difficult to manage these anastomosis strictures. Although some authors suggest the resection of this area with circular stapler for the treatment of anastomosis strictures [55], this may not always be possible, since stricture often includes a long colon segment, as in our 3 patients in high ligation group, and sometimes surgery might have to be terminated with an end colostomy, especially in anastomoses located below. Also it can be thought that diversion colitis might be contributed to the high anastomosis stricture rate (28.2%) in the high ligation group in our study.…”
Section: Discussionmentioning
confidence: 82%
“…Collagen I, a key component of the extracellular matrix, plays multifaceted functional roles in fibrotic processes, contributing to tissue scarring [ 46 ], organ fibrosis [ 47 , 48 ], and matrix remodeling [ 49 ]. Studies have indicated that fibrotic processes involving collagen deposition can contribute to the development of anal stenosis [ 50 ]. Additionally, the mechanical force can shift fibroblasts towards pro-fibrotic phenotypes, leading to myofibroblast differentiation and excessive collagen production driven by ERK-YAP activation [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that after dilation procedures, the anastomotic stenosis recurrence risk ranged from 5% to 20%. 13,24,25 Transanal digital dilation or Hegar dilation may be a useful complement to postoperative treatment. Regular colonoscopy is also necessary to evaluate anastomotic stoma and enable early intervention.…”
Section: Discussionmentioning
confidence: 99%